Desenvolvimento de produtos adoçados com rebaudiosideo-A e avaliação de propriedades funcionais e sensoriais - Carvalho, Ana Claudia Guilhen (2012)
: The leaves of the shrub Stevia rebaudiana (Bert.) Bertoni - a plant native to Paraguay - contain steviol glycosides (about 10 glycosides of steviol are often cited) which presents as main characteristic the high intensity of sweetness, being rebaudioside A (Reb-A) the most important. This substance as emerging as a new alternative of natural sweetener with quality in taste, free of calories, carbohydrates or fats, and is being rapidly gaining market especially after the fall of regulatory barriers imposed by the United States and Europe. In this work the performance of rebaudioside A present in new formulations of diet foods was compared with those of sucralose, an artificial sweetener that has excellent sensory profile and occupies 36% of the global market demand of high intensity sweeteners. The cranberry (Vaccinium macrocarpon Ait Ericaceae) is a fruit from the American family of berries, being rich in anthocyanins, flavonoids and proanthocyanidins, widely used as antioxidant, in the treatment of urinary infections, nonstick, with cancer-fighting properties, cardioprotective effects, hypoglycemic, and was used into the formulations of products developed in this work to incorporate functionality and/or nutraceutical properties. To develop formulations of diet jam and diet popsicle of strawberry enriched with cranberry and sweetened with Reb-A and sucralose to evaluate the properties regarding antioxidant activities, physical-chemistry characteristics, microbiological quality, and sensory evaluation.